Reporting violence against women in the Spanish and German press: A comparative study of cultural patterns - Bonachera Álvarez, Trinidad; Piñero Piñero, Gracia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Through a transdisciplinary theoretical framework, constituted, on the one hand, by the notions of culture and cultural standard and, on the other, by the approaches of critical discourse analysis, we carried out a contrastive study on the impact of cultural patterns on news articles about gender violence appearing in Spanish and German newspapers in 2019. The study is based on a corpus made up of news from the Spanish and German media that covers two events related to gender violence in which the two countries are involved. We examined five cultural dimensions that, according to scholars, oppose these two communities: material and factual orientation versus interpersonal orientation; rigidity versus relativization of norms; separation versus coexistence of the private and public sphere; individualism and abstract sense of the community versus feeling of belonging to the group; and, finally, and closely related to the previous pattern, the role given to the family in each of these communities. The examination of these five cultural patterns shows that the configuration of this textual genre is mediated by the social and cultural practices of those who produce it and those who receive it, since the divergences derived from the rules of regulation and behavior of each of these cultural spaces are evident.